Palliative Care Practice and Associated Factors Among Nurses Working in Chronic Care Units of Tertiary Hospitals in Ethiopia: A Cross-Sectional Study - Gembe M; Tariku T; Tesfaye T; Hailu EH (Dove Medical Press, 2024)
Maycas Gembe,1 Tizita Tariku,1 Temamen Tesfaye,2 Endalew Hailu Hailu2 1Department of Nursing, College of Health Science, Mattu University, Mattu, Ethiopia; 2School of Nursing, Faculty of Health Science, Jimma University, Jimma, EthiopiaCorrespondence: Maycas Gembe, Tel +251 936704900, Email MaycasDembelu27@gmail.comIntroduction: Palliative care is not yet widely available. Each year, approximately 58 million people worldwide require palliative care. In Africa, an estimated 9.7 million people require palliative care. In Ethiopia, the integration of palliative care into the country's health system has taken several years. Previous studies conducted on palliative care have emphasized on the knowledge of nurses towards palliative care, and some studies have attempted to assess the practice of palliative care in specific areas of the country. However, we studied the practice of palliative care at a national level. So, the purpose of the study is to identify nurses' palliative care practice level and factors associated with palliative care.Methods: We employed a facility-based cross-sectional study design to assess palliative care practices. We considered tertiary hospitals with functional cancer centers. To conduct this study, we included nurses from three hospitals; we recruited 255 nurses from these hospitals. The dependent variable of palliative care practice of nurses was first measured in continuous scale measurement and then converted to dichotomous outcome variable based on a 75% score cutoff value. Based on the multivariable logistic regression output, we considered variables with a p-value of < 0.05 as the factors significantly associated with good palliative care practice.Results: We collected data from 249 nurses, with a response rate of 98%. Based on our findings, 57% of nurses had good palliative care practices. We also identified that the type of healthcare facility, nurses' knowledge of palliative care, nurses' level of academic qualification, and nurses' attitudes towards palliative care were factors associated with the level of palliative care practice.Conclusion: This score of palliative care practice level should be improved. The Federal Ministry of Health, along with healthcare facilities in general and tertiary hospitals in particular, should strengthen good palliative care practice by providing up-to-date training for nurses.Keywords: palliative care, nurses, tertiary hospital, Ethiopia